Ordinances of the Police Jury for the Better Regulation of the Town of Clinton, Police Jury September Session 1847, sec. 1. (September session, 1847), at 680 (John C. White, Whig Office, September 1, 1848) - (:unkn) unknown (General Publisher, 1847)
Prohibited shooting firearms in the Town of Clinton.
--
Keywords: DISCHARGE